New Media Narratives and Visualization as an Alternative to Traditional Media: Youtuber Barış Özcan Sample - Ökmen, Yunus Emre (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
The traditional storytelling has begun to disappear, as the modern culture seizes every aspect of life (Ramsden and Hollingsworth, 2017: 14). The narrators began to take the place of digital media such as photography, cinema, television and internet. At the same time, basic cultural periods in communication can be handled in five different ways. These; Oral culture, written culture, printed culture, electric and electronic culture were finally added to these cultures or periods Digital culture, different media tools were introduced in the forms of communication between people and people (Baldini, 2000: 6). The traditional storytelling that started in the oral culture period has been moved to a different dimension with the applications on the web during the digital culture period. Thus, storytelling has experienced many changes and transformations in structural and content.